Relasi Komunikasi Ibu dan Anak pada Kasus Perilaku Kecanduan Game Online di Sekolah Dasar - Salman Alfarisyi Lesmana (UPT Publikasi Ilmiah UNISBA, 2026)
Abstrak. Today, cases of online game addiction are a matter of concern, particularly due to their impact on children's daily lives and behavior. Children who are emotional, withdrawn, and procrastinate on daily activities have become an interesting topic of discussion from a psychological perspective. Democratic communication is certainly a solution, and this also aligns with what experts and specialists have said. Mothers' involvement in their children's digital world is a crucial requirement today.The research design used a case study because the focus of the research was directed at an in-depth understanding of a specific phenomenon in a real-life context, namely the mother-child communication relationship in dealing with online game addiction. The research subjects consisted of two mothers as key informants, both of whom have elementary school-aged children with indications of online game addiction, and an expert informant, an elementary school guidance and counseling psychologist, who served to enrich perspectives and strengthen the validity of the findings through source triangulation. The results showed that communication patterns that emerged to prevent and reduce online game addiction between mothers and children typically began with an educational and persuasive communication approach. An effective strategy from a mother's perspective towards children is a democratic communication strategy so that children are also involved in expressing their opinions so that discussions and negotiations can take place, but it does not rule out the possibility that authoritarian and coercive strategies can also be applied if they reach the stage of endangering children's development.